Peace in the valley [large type] - Irvin, Kelly (Irvin, Kelly, Amish of Big Sky Country, 2021)
"Nora Beachy loves her life. She works in the community store in West Kootenai, takes care of her family and courts with Levi Raber. She and Levi plan to marry, but Levi wants to wait until he has the money to buy them a house before he pops the question. Nora doesn't want to wait. Is there something keeping Levi from marrying her? Nora's peaceful existence is swept away when wildfires threaten her family's home. She's forced to evacuate to Libby where she stays with family in an Amish community that embraces a charismatic style of worship rejected by her own parents and the Kootenai district elders. Nora's drawn to the emotional, powerful style of worship, the musical instruments, and the more relaxed lifestyle. She knows she's headed for a shunning if she doesn't stop breaking the rules, but she can't understand why both forms of worship aren't lovely in God's eyes. Nora's stuck in the middle. She loves her family and doesn't want to lose them. She loves Levi. But she must make a decision: return to her traditional Amish life or embrace this new way of worshipping and living. Will she sacrifice her relationship with Levi and her family for a different kind of faith?" --